PEMBERIAN EDUKASI KEPADA ORANG TUA DAN KADER DALAM PEMBERIAN VARIAN MENU MAKAN PADA BALITA UNTUK MENURUNKAN STUNTING DI PUSKESMAS ALUH-ALUH BESAR - Deananda; Syahrida Wahyu Utami; Nur Cahyani Ari Lestari (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Ibnu Sina, 2026)
Stunting is a serious public health problem in Indonesia, with prevalence reaching 21.5% in 2023. Banjar District,South Kalimantan, recorded a stunting prevalence of 30.1%, well above the national target of 14% in 2024. Thiscondition is caused by various factors, including inadequate parenting patterns, insufficient nutritional intake, andlimited parental knowledge about providing varied food for children. This community service activity aims toprovide education to parents and cadres about providing varied menu options for toddlers to reduce stunting inthe working area of Aluh-Aluh Besar Health Center, Banjar District. The method used is educational outreachwith leaflets and flip charts, accompanied by interactive discussions with participants. The activity involved 41participants, consisting of parents and posyandu cadres. The results of the activity showed an increase inparticipants' understanding of the importance of providing varied food containing balanced nutrition, the role ofparenting in stunting prevention, and exclusive breastfeeding practices. Activity outputs include seminar resultsand journal publications in accredited national journals. In conclusion, educating parents and cadres is animportant intervention in efforts to prevent and reduce stunting in the community.